Factor analysis of the decreasing youth interest and its contribution to the sustainable agriculture sector: Analisis Faktor-faktor yang Mempengaruhi Minat Generasi Muda terhadap Keberlanjutan Sektor Pertanian - Tafarini, Meitry; Tri Yuliani, Maulidia; Wardani, Azqia; Sari, Yulia; Fuji Lestari, Etika; Ilham Pamungkas Susilo, Ade; Amelia, Fadila; Manurung, Gugun (Departement of Socio-Economic Agricuture, Faculty of Agriculture, 2024)
The youth have a strategic role to play in driving the progress of the agricultural sector. Their interest in agriculture has become a critical concern for the continuity of this sector. This study aims to identify the factors determining youth interest in the agricultural sector. The respondents of this study comprised 50 individuals aged 14 to 29 years. The research use scoring methods and statistical analysis using logistic regression. The results show that youth interest in the agricultural sector is influenced by age, gender, opportunities, and challenges within the sector. Older respondents demonstrated a higher interest in agriculture. Male youth exhibited greater interest compared to female youth. Furthermore, the availability of opportunities within the agricultural sector was positively associated with youth interest. Conversely, an increase in challenges within the sector led to a decline in youth interest in agriculture.